2003
DOI: 10.1161/01.cir.0000065227.04025.c2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ventilatory Response to Exercise in Patients With Chronic Heart Failure and Central Sleep Apnea

Abstract: Background-In patients with chronic heart failure (CHF), central sleep apnea (CSA) and enhanced ventilatory response (V E/V CO 2 slope) to exercise are common. Both breathing disorders alone indicate poor prognosis in CHF. Although augmented chemosensitivity to CO 2 is thought to be one important underlying mechanism for both breathing disorders, it is unclear whether both breathing disorders are related closely in patients with CHF. Methods and Results-We investigated 20 CHF patients with clinically important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 40 publications
(48 reference statements)
5
58
2
1
Order By: Relevance
“…One reason for this could be that, after AMI, patients did not report daytime hypersomnolence. This finding is in accordance with previous reports demonstrating a dissociation of sleep apnoea from hypersomnolence in patients with cardiovascular disease such as HF and stroke [29][30][31]. Furthermore, in the present study, both groups have poor sleep efficiency, similar to previous studies of patients with chronic HF [30].…”
Section: Sleep-related Disorders S Buchner Et Alsupporting
confidence: 94%
“…One reason for this could be that, after AMI, patients did not report daytime hypersomnolence. This finding is in accordance with previous reports demonstrating a dissociation of sleep apnoea from hypersomnolence in patients with cardiovascular disease such as HF and stroke [29][30][31]. Furthermore, in the present study, both groups have poor sleep efficiency, similar to previous studies of patients with chronic HF [30].…”
Section: Sleep-related Disorders S Buchner Et Alsupporting
confidence: 94%
“…CSA events may also originate from unstable breathing control arising from the sleep-awake transition, as well as from cardiac or neurogenic causes (Naughton et al 1993). Periodic breathing patterns in patients with heart failure have been considered to be induced by instability of chemical control during sleep (Arzt et al 2003, Dempsey et al 2004. Unstable plant gain and controller gain cause a reduction in arterial CO 2 (PaCO 2 ) to a level below the apneic threshold, thereby resulting in central apnea.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, we found that severity of sleep apnea does not correlate with the novel indexes of CPX in cardiac patients with CSA. Although a ventilatory hypersensitivity to PaCO 2 is considered to be one of the key mechanisms for CSA, 24) the severity of sleep apnea did not correlate with the VE/VCO 2 slope obtained from CPX, which is considered to reflect central chemosensitivity to CO 2 . 25) Although PETCO 2 both at rest and at peak exercise, a parameter reflecting PaCO 2 , significantly correlated with the indexes of cardiopulmonary exercise testing, it did not correlate with the severity of sleep apnea.…”
Section: Discussionmentioning
confidence: 88%
“…Hypopnea was defined as a > 50% reduction of airflow or thoracoabdominal excursions lasting ≥ 10 seconds along with a ≥ 3% drop in pulse oximetric saturation. [22][23][24] CSA was defined as a cessation of thoracoabdominal excursions. OSA was defined when nasal airflow was absent despite the presence of thoracoabdominal excursions.…”
Section: )mentioning
confidence: 99%